Natural feeding and its effects on the intestinal health of dogs and cats: A literature review (Research, Society and Development, 2024)
Natural feeding has become an increasingly popular alternative to commercial kibble among dog and cat owners, as it is associated with several benefits for their pets' intestinal health. This type of diet is composed of fresh, minimally processed, and often raw foods, aiming to resemble the natural diet these pets would consume in the wild. Intestinal health is crucial to the animal's well-being, directly influencing digestion, nutrient absorption, and immune response. This study aims to review the existing scientific literature on the effects of natural food on the intestinal microbiota and gastrointestinal function of dogs and cats. The analysis focuses on identifying patterns and trends in the findings of different studies, while also highlighting knowledge gaps and areas that require further research. The results aim to assist pet owners and veterinary professionals make informed nutritional decisions for a more suitable and healthy pet diet.